Native Atherosclerosis and Vein Graft Arterialization: Association with Increased Urokinase Receptor Expression In Vitro and In Vivo - Okada, S. Steve; Golden, Michael A.; Raghunath, P. N.; Tomaszewski, John E.; David, Mary L.; Kuo, Alice; Kariko, Katalin; Barnathan, Elliot S. (Thrombosis and Haemostasis, 1998)
Interaction of proteases with cell surface receptors may modulate cell adhesion, migration, invasion, and matrix degradation. Since the plasminogen activator system has been hypothesized to play a role in intimal thickening after various types of vascular injury, we first studied the expression of urokinase receptor (u-PAR) protein and mRNA by smooth muscle cells (SMC) grown in explant cultures from normal and diseased vessels. Using equilibrium binding studies with radiolabeled 125I-labeled single chain urokinase-type plasminogen activator (scu-PA), we determined that SMC cultured from atherosclerotic arteries expressed a higher maximal number of binding sites/cell (3.6 ± 0.4 × 105 sites/cell vs. 2.1 ± 0.3 × 105, ± SEM, p <0.05) with a similar affinity (Kd = 1.5 ± 0.1 vs. 1.2 ± 0.2 nM, p = ns). However, SMC subcultured from diseased saphenous vein grafts expressed the highest levels of u-PAR compared to SMC from normal saphenous vein (4.8 ± 0.6 × 105 sites/cell vs. 1.6 ± 0.9 × 105, ± SEM, p <0.05). Using binding studies and Northern analysis, we demonstrated a dose and time dependent upregulation of u-PAR protein and mRNA expression respectively in human SMC in response to serum stimulation. Using a rabbit specific u-PAR cDNA probe, we demonstrated a similar upregulation of u-PAR mRNA both in rabbit aortic SMC in culture in response to serum stimulation and up to a 20 fold increase in u-PAR mRNA in rabbit jugular veins in response to implantation as arterial grafts in vivo. Finally, to confirm that u-PAR mRNA is upregulated in human vessels after injury, we performed immunohistochemistry and in situ hybridization studies on coronary arteries, normal saphenous veins and saphenous veins from 10 weeks to 13 years after implantation as grafts. u-PAR mRNA was found mainly in the periadventitial microcirculation in normal veins, but was found to be upregulated in the neointima and media of thickened veins in both macrophages and smooth muscle cells. SMC near the internal elastic laminae in diseased coronary arteries appeared to express increased u-PAR mRNA. These data suggest that this increased expression of u-PAR may contribute to early lesion development.